THE RELATIONSHIP OF PRAYER AND PATIENCE AS AN ANALYSIS HELP QS. AL-BAQARAH VERSE 153 - Putri Rizki Aini; Yuliyani (Sean Institute, 2023)
Writing this journal aims to find out how prayer and patience can be used as helpers as contained in QS. Al-Baqarah/2:153. By using the method of library research library research, the author collects data from the Al-Qur'an and translations as well as various other literary materials related to the theme and then elaborates it. After conducting a literature study, it can be concluded that humans as His servants will always be tested through grace or calamity. A person who has faith will be able to see the wisdom behind every incident he experiences, by being patient and praying every day. Indeed, with patience and prayer, Allah will help His servant, so that no one can change his decree except only with the permission of Allah Subhanallahuwata'ala